(untitled) (UNIZIK Journal of Agricultural Economics and Extension, 2024)
The importance of organic fertilizer such as crop residues cannot be over emphasized or overrated particularly in the production of cereal crops such as sorghum. The effect of crop residues on sorghum output was unknown due to its poor usage. There also exist limited empirical evidences on what effect crop residues have on sorghum output in the northern part of Nigeria. This study was carried out to know the effect of crop residues on sorghum output in Zamfara and Sokoto States, Nigeria. A multi-stage sampling technique was used to select 160 farmers in Sokoto State and 150 farmers in Zamfara State with a total of 310 sorghum farmers selected from the study area. Data were collected with the aid of structured questionnaire and personal interviews. Data collected were analyzed using the four functional forms of OLS regression model (linear, exponential, semi-log and log-log models). The findings revealed that farm size, quantity of crop residue applied, quantity of sorghum seeds planted, quantity of agro-chemicals used, farm income and crop residue access were statistically significant on sorghum output in the study area. The results also showed that with trials of the four functional forms of the OLS regression and based on the R2-values, the F-statistics, signs and magnitudes of the coefficients and the number of variables that were significant, the log-log model was selected as the lead equation and most fit for the OLS regression in the study area. The study recommended adoption of crop residue technology, increase in the quantity of sorghum seeds planted and training of sorghum farmers to improve on adoption of crop residue technology through extension services.